Pengaruh Promosi Penjualan Dan Kualitas Layanan Terhadap Loyalitas Konsumen Fanatic Coffee Bogor - Kusumayanti, Diah; Christie G. B., Giovanno; Mulyana, Mumuh (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The growth of coffee shops, especially in the city of Bogor at this time is very rapid, giving rise to trade competition for each coffee shop in order to get consumers who are loyal to the coffee shop itself. Every coffee shop competes to get consumers who are loyal to the coffee shop. The purpose of this study was to analyze the effect of sales promotion and service quality on customer loyalty at Fanatic Coffee Bogor. The number of respondents was 175 respondents who were taken using a questionnaire. Processed with SPSS version 20, the results of the study are (1) Sales Promotion has a positive and partially significant effect of 5.462. (2) Service quality has a positive and partially significant effect of 10.326. (3) Sales Promotion and Service Quality together have a positive and significant effect simultaneously of 188,412 on Customer Loyalty. So it can be concluded that in this study the variables of Sales Promotion, and Service Quality play a role or contribute to Customer Loyalty with an R-square value of 68.7% while the rest is explained by other variables. Keywords : Sales Promotion, Service Quality, Customer Loyalty